The therapeutic effect of PCSK9 inhibitors on dyslipidemia: one-year follow up - Maryam Moshkani Farahani; Alireza Nasiri; Mahdi Salari; Ali Shamsedini (PAGEPress Publications, 2024)
Despite the availability of statins and lifestyle modifications, many patients with Dyslipidemia struggle to achieve optimal low-density lipoprotein cholesterol (LDL-C) control. PCSK9 inhibitors offer a promising new therapeutic option with superior LDL-C lowering efficacy compared to statins. However, data on their real-world use, particularly in Iran, is limited. This study aims to address this gap by investigating the one-year effects of evolocumab on lipid profiles and potential cardiovascular outcomes in Iranian patients with Familial Hypercholesterolemia (FH).This single-center, prospective study evaluated evolocumab effectiveness in lowering LDL-C in 50 Iranian adults with FH. Participants with a documented LDL-C > 190 mg/dL on existing cholesterol medications (excluding PCSK9 inhibitors) and a clinical FH diagnosis was included. After baseline assessments (medical history, demographics, lipid profile), evolocumab was administered subcutaneously every two weeks for one year. Follow-up assessments at year one measured changes in LDL-C, high-density lipoprotein cholesterol (HDL-C), and triglycerides. The study enrolled 50 participants with an average age of 55 years old (range 35-80 years).Treatment with evolocumab led to significant improvements in lipid profiles at all follow-up points compared to baseline. On average, LDL-C levels decreased by 105.24 mg/dL, triglycerides decreased by 59.20 mg/dL, and HDL-C levels increased by a modest but significant 4.5 mg/dL after one year(p<0.001). Subgroup analysis revealed no statistically significant interactions between baseline demographics (age, sex, BMI) or lifestyle habits (smoking, alcohol) and changes in lipid levels(p>0.05). However, a significant interaction emerged between baseline lipid levels and their corresponding reductions, suggesting greater improvement in patients with higher baseline values(p<0.05). It is noteworthy that no new cardiovascular events were reported during the study period. This study demonstrates the effectiveness of evolocumab in improving lipid profiles in Iranian patients with FH. The observed reductions in LDL-C and triglycerides, along with a modest increase in HDL-C, suggest potential benefits for cardiovascular risk reduction. The absence of new cardiovascular events during the study is encouraging, but further research with larger and longer-term follow-up is needed to confirm these findings and assess the long-term safety and impact on quality of life.